Effect of Parijoto (Medinilla speciosa) Fruit Nanoparticle Extract on Physicochemical Properties, Microstructure, and Functional Characteristics of Yogurt - Simanjuntak, Tirza Lamtiar Anastasia; Setyowati, Ayumi; Sari, Widya Yuni Puspita; Habibah, Vindy Nur; Dewi, Cecilia Shinta; Saleha, Rischa Amalia; Fardiaz, Dedi (Faculty of Animal Science Universitas Brawijaya, 2026)
Milk is a widely consumed and nutritious food, while parijoto fruit (Medinilla speciosa) contains bioactive compounds such as flavonoids, tannins, alkaloids, saponins, and anthocyanins with antioxidant and antimicrobial properties. However, the effectiveness of these compounds may decrease when incorporated into dairy products. Nanoparticle technology offers a promising approach to enhance their stability, availability, and functionality. This study aimed to evaluate the effects of parijoto fruit extract nanoparticles on the physicochemical, microbiological, microstructural, mineral, and functional properties of yogurt. The experiment used a Completely Randomized Design (CRD) with five concentrations of parijoto extract nanoparticles (0%, 2.5%, 5%, 7.5%, and 10%) and four replications. Yogurt was produced using Streptococcus thermophilus and Lactobacillus bulgaricus as starter cultures. Observed parameters included pH, moisture content, soluble protein, total lactic acid bacteria (LAB), total titratable acidity, color characteristics (L*, a*, b*), antimicrobial activity against Escherichia coli and Salmonella typhi, antioxidant activity (DPPH), microstructure, and mineral composition. Data were analyzed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) or non-parametric tests when appropriate. Results showed that nanoparticle addition significantly affected (p < 0.01) pH, total LAB, color, antioxidant activity, microstructure, and mineral profile. Increasing concentrations lowered pH (3.95–3.62), reduced LAB counts, and enhanced antioxidant activity, with the strongest effect at 10% (IC?? 38.57 ppm). Other parameters showed no significant differences. Overall, parijoto extract nanoparticles improved yogurt functionality and quality, indicating strong potential as a functional dairy ingredient.